Does Faith Make You Healthy and Happy?: The Case of Evangelical Christians in the UK - Smith, Greg (The journal of religion & society, 2017)
The science of happiness is a developing field which attempts to measure the health and emotional well-being of populations by reliable social survey techniques. One strand of research suggests that religious practice (believing and belonging) are positively associated with well-being measures. This paper assesses new evidence on the relationship between religiosity and the different dimensions of well-being (hedonic and eudaimonic). It makes direct comparisons between an opportunity sample of Evangelical Christians in the UK, and the reports of UK Office of National Statistics surveys of representative samples of the UK population. Evangelicals do show high scores on many standard indicators, with differences from the national population on eudaimonic scales that reach statistical significance. Their lifestyles are generally consistent with good health and well-being outcomes. However, when age profiles and income/social class are considered it remains to be established whether evangelical faith adds significant and measurable value to people’s health and well-being, at least within this mortal life.